Removal of phenols by adsorption on fly ash - Kumar S.; Upadhyay S.N.; Upadhya Y.D. (My University, 2025)
Adsorption of phenol and cresol and their mixtures from aqueous solutions on activated carbon and fly ash has been investigated. The effects of contact time and initial solute concentration have been studied and isotherm parameters are evaluated. The Freundlich isotherm has been found to be more suitable for all the systems investigated. Copyright © 1987 Society of Chemical Industry